Factors influencing the entrepreneurial behaviour of agricultural graduates - Chandrashekar, S; Bahal, R; HD, VP (SAARC Journal of Agriculture, 2014)
The study is to assess the performance of Agri Clinic entrepreneurs promoted under the scheme on Agri Clinic and Agri Business Centers in India. Thus an attempt has been made to evolve a set of factors influencing the entrepreneurial behaviour through a data reduction process of factor analysis. The factors include: planning orientation, work orientation, personal efficacy, market orientation, location, business acumen, dynamism, service orientation, in-depth knowledge, achievement motivation, social networks, interest, internal control, marketing strategy and innovativeness. The factor analysis brought out results that appeared to be in conformity with the existing theory of entrepreneurial motivation and entrepreneurial behaviour patterns of successful entrepreneurs. DOI: http://dx.doi.org/10.3329/sja.v10i2.18321 SAARC J. Agri., 10(2): 31-39 (2012)